REAKSI INVESTOR TERHADAP INFORMASI PENINGKATAN KASUS HARIAN COVID-19 PADA EMITEN PENYEDIA JASA KESEHATAN BEI - Fathoni, Imam; Fadli, Faishal (Contemporary Studies in Economic, Finance and Banking, 2023)
COVID-19 pandemic have impact on the economy, We can see from the IDX stock market crash, that can be observed from january 2020 untill march 2020. When COVID-19 pandemic occur, there was an increase demand for health product. That can be showed by how the company revenue increased on health service company, then how the investor respond to that?. This study aims to observe the investor reactions, on increasing COVID-19 cases to returns, abnormal returns and trading volume activity of Health Service Providers based company,  with a period of 10 days before and after the announcement of the event. This study uses an Event Study approach. The result of this study is that there are significant differences in the before and after period on return and abnormal return, and not significant on trading volume activity variables. There are three implications obtained from this study, the first is that this research confirms that information affects stock prices. The second implication is that the significant increase in returns and abnormal returns does not mean that trading volume activity has also increased significantly. The final implication of this research is that the alleged inclination of investors irrationality.